Clinical impact of the flattening filter free irradiation in fixed-field IMRT and VMAT for stage I–II nasal natural killer/T-cell lymphoma. Issue 1 (1st January 2021) - Liu, Xianfeng; Jin, Fu; Luo, Huanli; Zhang, Xin; Guo, Mingfang; Zhao, Xiujuan; Wu, Furong; Guo, Qishuai
ABSTRACT: The study aimed to investigate clinical impact of the flattening filter free (FFF) irradiation in fixed-field intensity-modulated radiotherapy (IMRT) and volumetric-modulated arc therapy (VMAT) for patients with stage I–II nasal natural killer/T-cell lymphoma (NNKTCL). Four different plans, fixed-field IMRT, and VMAT plans with and without flattening filter (FF) (IMRT FF, IMRT FFF, VMAT FF, and VMAT FFF) were created for each of selected patients. Target quality, organs at risk (OARs) sparing, and tumor control probability (TCP) were compared between IMRT and VMAT with and without FF. The values of D98%, V95%, and conformal index were 0.03 Gy ( P = 0.028), 0.03% ( P = 0.048), and 0.002 ( P = 0.002) lower with IMRT FFF than with IMRT FF, and the values of D2%, Dmean, and homogeneity index were 0.14 Gy ( P = 0.018), 0.1 Gy ( P = 0.007), and 0.002 ( P = 0.008) higher with VMAT FFF than with VMAT FF. The TCP was higher with FFF beam than flattened beam in IMRT and VMAT. The results show that FFF irradiation achieved slightly worse target quality than FF irradiation in IMRT and VMAT for stage I–II NNKTCL. FFF beam was advantageous to increase the TCP in IMRT and VMAT.